Construction of a sequentially responsive nanocarrier for chemotherapy and cascade amplified NIR photodynamic therapy. Issue 10 (12th January 2022) - Yan, Tao; Ren, Linlin; Li, Fengyan; Tian, Feng; Jiang, Chengfang; Wang, Qi; Song, Xinyue; Zhang, Shusheng
Abstract : A nanotheranostic agent was prepared using UCNPs@mSiO2 /MB coated with a DNA nanoshell to construct tumor microenvironment responsive chemotherapy and cascade amplified PDT. Abstract : A sequentially responsive nanocarrier was fabricated with three-in-one functional integration: bio-imaging, tumor microenvironment responsive chemotherapy and cascade activation of upconversion photodynamic therapy. The designed DNA outer nanoshell displayed site-specific degradation and controlled degradation speed. Significantly, the developed controllable nanotheranostic agent displayed high cell apoptosis ratios and obvious tumor inhibition.